Agricultural Productivity, Diversification and Gender : Background Report to Sri Lanka Poverty Assessment - World Bank (World Bank, Washington, DC, 2021)
Identifying opportunities to increase agricultural productivity and incomes is an important priority for rural development. Progress toward poverty reduction continued in recent years, but the contribution of the agriculture sector was weak, mainly because productivity improvements were relatively limited. Using detailed individual-level data on agricultural activities, this paper analyzes agricultural production patterns and associated productivity of farm households. Particular attention is paid to (i) diversification toward higher-value, export-oriented crops as a means to increase productivity and earnings; and (ii) gender differences in farming activities and outcomes. The role of structural factors such as access to land is also considered. There are three key findings in this paper. First, diversified farmers, especially those with a crop mix that is focused on export crops or other high-value crops have higher productivity and earnings. The productivity of paddy cultivation is significantly lower than that of other crops, leading to low earnings. Second, production patterns and productivity levels differ distinctively between men and women farmers. Female farmers have higher productivity, as measured by output value per acre, which is mainly explained by their smaller plot size and a crop mix that consists of higher-value crops. However, despite higher productivity, overall farm incomes are lower among female farmers, mainly due to lower access to land. Third, once land size and crop mix are accounted for, unequal access to resources eventually leads to a male productivity advantage, referred to as conditional advantage, after differential access to resources is controlled for via multivariate analysis. Policies to increase the crop mix toward higher-value, export-oriented crops and to equalize access to resources, including land and agricultural inputs, could help improve productivity and income, and reduce gender disparities.